The role of Cognitive linguistics in Kazakhstan: conceptualization and categorization (Eurasian Journal of Philology Science and Education, 2024)
From time immemorial, man deeply interacts and contacts with the environment and society, builds and adds up his certain idea of ​ ​ the world, forming a linguistic model of understanding and understanding of the world, which is called the picture of the world. The picture of the world is one of the component definitions that describe human being, the global image of the world and a certain vision of the world in accordance with the logic of world understanding. Learning the world, a person learns to display and also perceive in the mind the positions of a reflecting subject, which leads to the comprehension and emergence of the language model of the world, in particular the language picture of the world. By gaining experience, transforms it into certain concepts, which, logically connecting with each other, form a conceptual system; it is constructed, modified and refined continuously by humans. This is explained by such a property of the concept as the ability to variability in consciousness. Concepts, being part of the system, fall under the influence of other concepts and are themselves modified. The number of concepts and the amount of their content change over time. This article considers a number of linguistic concepts that were determined and formed during the interaction of the language and culture of the Asian linguocultural community, which represents national-cultural worldview and worldview, in general, since each civilization and social society is characterized by its own unique way of perceiving the world.Keywords: the language of the world, categorization, conceptualization, metaphor, metaphorical process.